The Nexus between Consumer Confidence and Economic Growth in South Africa: An ARDL Bounds Testing Approach - Madlopha, Khayelihle (Journal of Economics and Behavioral Studies, 2019)
Consumption expenditure contributed a total of 2.2% to economic growth in 2017. Hence, the South African economy is consumption driven. Therefore, there is a need to understand the growth-economic confidence relationship within the South African context. In this spirit, this paper set to explore the short- and long-run relationship between consumer confidence and economic growth in South Africa for the sample period 1994Q1 to 2017Q4. The method applied, chiefly because our variables were I (0) and I (1) and that we sought short- and long-run estimates were the Autoregressive Distributed Lag (ARDL) model using the bounds testing procedure. The results showed that consumer confidence contributed about 0.025% to economic growth in the short-run, and about 0.4% in the long-run. The results suggest that boosting consumer confidence should be keys for South African policy-makers to boost growth in the short- and long-run. In particular, we recommend policy certainty and political stability as some of the ways to attract consumer confidence.